The anatomy of Communist takeovers - edited by Thomas T. Hammond ; associate editor, Robert Farrell ; foreword by Cyril E. Black. (Yale University Press, 1976)
First published as Volume XI, Number 4, 1971, of Studies on the Soviet Union. Includes index and bibliography: p. [649]-652.